The Effectiveness of Peer Support Based on Islamic and Muhammadiyah Values on Nutritional Intake and Hemoglobin Levels in Adolescent Girls - Meta Rikandi; Asmeri Lamona; Suci Sintia Dewi; Desi Asmaret; Linda Wati; Afrira Esa Putri (Fakultas Keperawatan Universitas Andalas, 2026)
Iron deficiency anemia is a significant public health challenge, particularly among adolescent girls in foster care institutions. This study aims to evaluate the effectiveness of a peer support program integrated with Islamic and Muhammadiyah values in improving nutritional intake and hemoglobin (Hb) levels in adolescent girls at the 'Aisyiyah Nanggalo Orphanage, Padang. A quasi-experimental research design was used from September to December 2025, involving 30 respondents selected through a total sampling technique. The intervention was carried out through intensive mentoring by peer mentors who focused on nutritional education and strengthening spiritual aspects, by making health maintenance a form of worship. The results showed a significant increase in AIK knowledge (from 66.7% to 90.0% in the good category) and an increase in micronutrient consumption patterns by 12.85%, where iron intake increased from 36.05 mg to 76.05 mg. However, the Wilcoxon Signed Rank test yielded a p-value of 0.590 (p > 0.05), indicating no statistically significant difference in hemoglobin levels before and after the intervention. Although it has not had a clinical impact on Hb levels in the short term, this program is practically effective in improving knowledge and discipline in daily nutritional intake. Therefore, peer mentoring based on religious values remains an important and sustainable strategy for improving the health behaviors of adolescent girls in institutional settings.